Severe hyponatremia as presenting symptom of small cell lung carcinoma. (27th January 2023) - Stevchevska, Aleksandra; Milenkovic, Tatjana; Todorova, Biljana; Jovanova, Sasha Mishevska; Bajraktarova, Tatjana Prosheva
Abstract: A 62-year-old female patient was admitted to ICU in our clinic with symptomatic severe hyponatremia with complaints of fatigue, vertigo, paresthesia of upper extremities and three episodes of loss of consciousness in the past month. She had been hospitalized two weeks before in neurology clinic because of the same symptoms. CT of the brain, EEG, ophthalmology examinations were negative. She did not complain of hemoptysis, cough, weight loss, fever, chest pain or dyspnea. Nephrologist was consulted and renal origin of the hyponatremia was excluded, before admission. Initial laboratory tests were glucose:5, 47 umol/L, sodium:109 mEq/L, potassium;4.5 mEq/L, urea 3, 9 umol/l;creatinine:52, 7 mol/l, calcium:1, 22umol/L, TSH 5;Cortisol 819nmol/L;ACTH:16, 34 pg/ml. Her medical history included hypertension, primary hypothyroidism and history of smoking. Upon laboratory findings of low serum osmolality, high urine osmolality, high urine sodium levels and clinical euvolemia, and in the absence of renal, pituitary disfunction, adrenal insufficiency, inappropriate ADH syndrome was diagnosed and initially was treated with 3% NaCl. Since this treatment had no effect, it was started with fluid restriction, per os sodium intake was increased and therapy with loop diuretic was initiated, which resulted in correction of the hyponatremia. For the etiology consideration of inappropriate ADH syndrome CT of the thorax was performed, which revealed a neo infiltrative process with atelectasis in the poster basal segment of the left lobe. Histopathological sampling from the biopsy of the mass revealed small cell carcinoma of the lung. Metastasis were not detected. Since basal morning cortisol level was above upper range, with inappropriate measurements of ACTH constantly above 15 pg/ml, additional tests for ectopic Cushing syndrome were done. Overnight 1mg dexamethasone suppression test showed absent suppression of the morning cortisol values of 656nmol/L and ACTH of 22, 14 pg/ml and absent circadian rhythm of cortisol secretion, with high measurements of midnight serum cortisol of 652 nmol/L. Diagnosis of ectopic Cushing syndrome and SIADH as part of paraneoplastic syndrome in small cell lung carcinoma was made. It is to be noted that patient had no significant symptoms or signs of hypercortisolemia. We report here a case of small cell carcinoma of the lung whose first presentation was with symptomatic hyponatremia as a result of inappropriate ADH syndrome. The most common neoplasms associated with hyponatremia are various forms of lung cancer. Because of the aggressive nature of the disease, the most common manifestation of small cell carcinoma of the lung is a metastatic one. Therefore, identifying the disease in earlier stages is very important. Unfortunately, these patients have low rates of survival and face a very poor prognosis even with treatment. The presence and early identification of paraneoplastic syndromes can be beneficial in this context.